2010
DOI: 10.1002/jsfa.4163
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic acid B inhibits low-density lipoprotein oxidation and neointimal hyperplasia in endothelium-denuded hypercholesterolaemic rabbits

Abstract: The data obtained in this study suggest that Sal B protects HAECs from oxidative injury-mediated cell death via inhibition of ROS production. The antioxidant activity of Sal B may help explain its efficacy in the treatment of vascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 41 publications
4
47
0
1
Order By: Relevance
“…The results of the present study indicated that salvianolic acid B exerts protective effects against LPS-induced oxidative stress in ALI rats. Yang et al (14) suggested that salvianolic acid B protects against low-density lipoprotein oxidation and neointimal hyperplasia through inhibition of reactive oxygen species production in endothelium-denuded hypercholesterolaemic rabbits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the present study indicated that salvianolic acid B exerts protective effects against LPS-induced oxidative stress in ALI rats. Yang et al (14) suggested that salvianolic acid B protects against low-density lipoprotein oxidation and neointimal hyperplasia through inhibition of reactive oxygen species production in endothelium-denuded hypercholesterolaemic rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was shown to have neuroprotective effects in rats with focal cerebral ischemic reperfusion (13). It has been suggested that theneural functional recoveryeffect of salvianolic acid B is dependent on its specific chemical structure, which are accountable for is neuroprotective effects (12,14). The present study assessed whether salvianolic acid B exerts a protective effect on LPS-induced ALI.…”
Section: Introductionmentioning
confidence: 91%
“…Inhibiting the formation of oxLDL is beneficial in preventing the development of atherosclerosis [28] . It was found that MLB inhibited serum LDL oxidation [24] , and MLB-treated LDL exhibited vitamin E-binding ability and was resistant to Cu 2+ -induced oxidation [21] . These studies suggest that MLB can attenuate pathological increases in the peroxidation of lipids, thus suppressing the development and progression of atherosclerosis.…”
Section: Animal Models Mechanisms Referencesmentioning
confidence: 99%
“…Rat model of carotid artery balloon injury ↓ Neointimal hyperplasia Pan et al [17] ↓ SDF-1α-stimulated cell proliferation and migration ↓ CXCR4 receptor ↓ Promoter activity of NF-κB ↓ Raf-1, MEK, ERK1/2, phospho-ERK1/2, FAK, and phospho-FAK Cholesterol-fed rabbits ↓ Cu 2+ -induced LDL oxidation in vitro Yang et al [24] ↓ HAECs-mediated LDL oxidation ↓ oxLDL-induced cytotoxicity and ROS production in HAECs ↓ Lipid deposition in the thoracic aorta ↓ Intimal thickness of the aortic arch and thoracic aorta ↓ Neointimal formation in the abdominal aorta…”
Section: Animal Models Mechanisms Referencesmentioning
confidence: 99%
“…Many pharmacological studies have discovered that salvianolic acid B (Sal B), a principal component of Salvia miltiorrhiza, is efficacious in curing cardiovascular disease (CVD) [12,13], a conclusion supported by US FDA phase II clinical trials. In addition, some researchers suggested that many cellular functions such as signal transmission are achieved by the mutual interaction of many biological modules, each with their own specific physiological function [14].…”
mentioning
confidence: 99%